2005
DOI: 10.1002/cphc.200400405
|View full text |Cite
|
Sign up to set email alerts
|

Complexes and Clusters of Water Relevant to Atmospheric Chemistry: H2O Complexes with Oxidants

Abstract: Experimental observations and data from quantum chemical calculations on complexes between water molecules and small, oxygen‐containing inorganic species that play an important role as oxidants in the atmosphere (O(1D), O(3P), O2(X3Σg), O2(b1Σg+), O3, HO, HOO, HOOO, and H2O2) are reviewed, with emphasis on their structure, hydrogen bonding, interaction energies, thermodynamic parameters, and infrared spectra. In recent years, weakly bound complexes containing water have increasingly attracted scientific attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 105 publications
4
82
0
Order By: Relevance
“…The peak intensities of SF 4 Figure 2(b) shows that the intensity of the OH peak decreased with the addition of water into the flow tube system, which was due to not only the loss of CIMS sensitivity as described above, but also to the conversion of OH into OH-water complexes. [17][18][19][20] In particular, the peak intensity of [OH(…”
Section: Resultsmentioning
confidence: 99%
“…The peak intensities of SF 4 Figure 2(b) shows that the intensity of the OH peak decreased with the addition of water into the flow tube system, which was due to not only the loss of CIMS sensitivity as described above, but also to the conversion of OH into OH-water complexes. [17][18][19][20] In particular, the peak intensity of [OH(…”
Section: Resultsmentioning
confidence: 99%
“…However, IR spectra and computational studies suggest that the H 2 O-O 2 complex is hydrogen bonded [47] (Fig. 9) rather than T shaped as in the case of ammonia dioxygen.…”
Section: Future Workmentioning
confidence: 99%
“…Recent studies have revealed that adsorbed water on the surface of aerosols in the troposphere affects heterogeneous reactions between radicals and aerosol particles (Park et al, 2008). Adsorbed water can also interfere with gaseous reactions in the troposphere by removing or blocking one or more of the reactants (Sennikov et al, 2005;Hansen and Francisco, 2002;Aloisio and Francisco, 2000). Due to its ability to form hydrogen bonds, water vapor clusters readily with various gaseous species.…”
Section: Introductionmentioning
confidence: 99%
“…No clear experimental evidence corroborates for the existence of such a complex, although theoretical studies have estimated its structure and energy (Karakus and Ozkan, 2005;Sennikov et al, 2005;Aloisio and Francisco, 2000;Wang et al, 1999;Dubey et al, 1997;Kim et al, 1991). Little is known of the rate constant and mechanism of the complex forming reaction of OH and H 2 O.…”
Section: Introductionmentioning
confidence: 99%